PENGARUH CONTENT MARKETING DAN ELECTRONIC WORD OF MOUTH (e-WOM) TERHADAP KEPUTUSAN PEMBELIAN MELALUI TIKTOK PADA MAHASISWA STAMBUK 2023 - Talenta Emma Renata Marbun; Erlianti Simanjuntak; Benyamin Nababan; Faisal Bimantaro Ompusunggu; Syerin Sihombing (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study aims to analyze the influence of content marketing and electronic word of mouth on purchase decisions through TikTok among students of the 2023 cohort of the Bachelor of Management Study Program, Faculty of Economics, Universitas Sisingamangaraja XII Tapanuli. This research employed a quantitative approach with a descriptive-causal design. The entire population of 76 students was used as the sample through a total sampling technique. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS version 26. The results show that content marketing has a positive and significant effect on purchase decisions, with a t-value of 4.870 and a significance level of 0.000. Electronic word of mouth also has a positive and significant effect, with a t-value of 6.186 and a significance level of 0.000. Simultaneously, both variables have a significant effect on purchase decisions, with an F-value of 47.498 and a significance level of 0.000. The coefficient of determination of 0.565 indicates that 56.5% of the variation in purchase decisions is explained by content marketing and electronic word of mouth, while the remaining 43.5% is influenced by other factors. These findings confirm the importance of relevant content strategies and credible user reviews in encouraging student purchase decisions through TikTok. Keywords: content marketing; electronic word of mouth; purchase decision; TikTok; students; digital marketing.   Abstrak: Penelitian ini bertujuan menganalisis pengaruh content marketing dan electronic word of mouth terhadap keputusan pembelian melalui TikTok pada mahasiswa Program Studi S1 Manajemen Fakultas Ekonomi Universitas Sisingamangaraja XII Tapanuli angkatan 2023. Penelitian menggunakan pendekatan kuantitatif dengan desain deskriptif-kausalitas. Seluruh populasi sebanyak 76 mahasiswa dijadikan sampel melalui teknik total sampling. Data dikumpulkan menggunakan kuesioner skala Likert dan dianalisis dengan regresi linear berganda menggunakan SPSS versi 26. Hasil penelitian menunjukkan bahwa content marketing berpengaruh positif dan signifikan terhadap keputusan pembelian dengan nilai t-hitung 4,870 dan signifikansi 0,000. Electronic word of mouth juga berpengaruh positif dan signifikan dengan nilai t-hitung 6,186 dan signifikansi 0,000. Secara simultan, kedua variabel berpengaruh signifikan terhadap keputusan pembelian dengan nilai F-hitung 47,498 dan signifikansi 0,000. Nilai koefisien determinasi sebesar 0,565 menunjukkan bahwa 56,5% variasi keputusan pembelian dijelaskan oleh content marketing dan electronic word of mouth, sedangkan 43,5% dipengaruhi faktor lain. Temuan ini menegaskan pentingnya strategi konten yang relevan dan ulasan pengguna yang kredibel dalam mendorong keputusan pembelian mahasiswa melalui TikTok. Kata Kunci: content marketing, electronic word of mouth, keputusan pembelian, TikTok, mahasiswa, pemasaran digital.